The development, validation and evaluation of persuasive gamification problem-based learning in medical curriculum - Ghani, Azril Shahreez Abdul (2024)
Problem-based learning (PBL) is a learner-centred approach that encourages students to acquire and apply knowledge and skills for lifelong learning. However, engaging students to learning activities in PBL can be challenging due to its complexity and the interplay of various variables. Persuasive gamification has emerged as an effective method in higher education, whereby game design elements has been used to enhance engagement and stimulate learning behaviours. Therefore, incorporating game design elements in the design of PBL instruction could be an effective way to engage students with the learning activities. This study aims to develop a valid and effective persuasive gamification PBL guideline for tutors and explore its impact on students learning. The Persuasive Gamification-Problem-based Learning (PG-PBL) framework was developed by utilising empirically proven strategies from two scoping reviews that explored effective learning behaviours and persuasive gamification elements in collaborative learning environment. The identified elements were incorporated into the Maastricht 7-step PBL approach which resulted in the PG-PBL 7-step with two additional steps—step prep and step add. The content, response process, and internal structure validity of PG-PBL were evaluated in several series of validity studies involving eight content experts and 12 PBL tutors. The effectiveness of the PG-PBL was investigated in a randomised controlled trial involving 27 participants from one public medical school in Malaysia, whereby PG-PBL was compared with the online PBL that utilised Maastricht 7-steps method. The impact of the PG-PBL on students’ cognitive load, engagement scores, and knowledge acquisition were investigated and their experience attending the PBL session were explored in several focus group discussions. There are no significant between group difference of the three constructs of cognitive load, despite higher intrinsic and self-perceived learning scores in PG-PBL group. In addition, The PG-PBL has large impact on reducing students’ extraneous load and moderate impact on self-perceived learning, whereby this approach engaged students to devote significant mental resources to form mental connections and schemata of the learned information. Furthermore, they exhibited greater cognitive and emotional engagement as compared to the control group, however the changes were not significant. The PG-PBL was observed to moderately affect students' cognitive engagement, which could have influenced the students understanding of the PBL content. The PG-PBL group outperformed the control group in knowledge acquisition, despite similar baseline knowledge. Qualitative analysis identified four categories reflecting student experiences which include characteristics of engaging PBL sessions, the benefits associated with such sessions, the factors that contribute to disengagement, and suggestions for enhancing engagement in PBL sessions. While the framework yielded positive outcomes, feasibility issues were addressed by the faculty members. Therefore, the researcher suggests a final version of the guideline, emphasising students' familiarity with the PG-PBL framework. This effort empowers students to take ownership of their education, fosters critical thinking and problem-solving, and promotes collaboration and teamwork.